Identification of Mineral Absorption in the Meat of Freshwater Kijing (Pilsbryoconcha exilis Lea) Using X-Ray Fluorescence (XRF) - Sartika, Sartika; Adam, Moh. Awaudin; Ariyanti, Dwi (Research and Social Study Institute, 2024)
The filtration ability of freshwater mussels is used as an indicator of biofiltration and has the potential to accumulate various minerals and heavy metals. This study aims to identify minerals resulting from absorption in the meat of freshwater kijing (Pilsbryoconcha exilis Lea) using the X-Ray Fluorescence (XRF) technique. Meat freshwater kijing sliced thinly and carried out the drying process below ray sun direct in 3 days with objective lower water content. Samples already dry smoothed with method pounded using mortar until smooth and filtered for get sample form flour meat tombstone. Method of quantitative identification of absorbed minerals in samples was carried out using the X-Ray Fluorescence method (ED-XRF type) Rigaku NexCG type. The XRF testing procedure is carried out in several steps. The results of the research show that qualitatively, in the XRF test, freshwater kijing meat contains 29 metal elements with the top 10 elements consisting of calcium oxide (CaO), calcium (Ca), phosphorus pentoxide (P2O5), phosphorus (P), manganese oxide. (MnO), sulfur trioxide (SO3), manganese (Mn), silicon dioxide (SiO2), aluminum oxide (AlO), magnesium oxide (MgO). Meanwhile, quantitative analysis shows that the five most abundant metal elements are CaO 48.70%, Ca 34.80%, P2O5 30.90%, P 13.50%, and MnO 4.9%. These results show that the main mineral compiler meat freshwater kijing is calcium and phosphorus. Element calcium and phosphorus lots utilized freshwater kijing for preparation shell.